2002
DOI: 10.2337/diabetes.51.10.2968
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Thiazolidinediones on Plasma Adiponectin Levels in Normal, Obese, and Type 2 Diabetic Subjects

Abstract: The insulin-sensitizing effects of thiazolidinediones are thought to be mediated through peroxisome proliferator-activated receptor-␥, a nuclear receptor that is highly abundant in adipose tissue. It has been reported that adipocytes secrete a variety of proteins, including tumor necrosis factor-␣, resistin, plasminogen activator inhibitor-1, and adiponectin. Adiponectin is a fat cellsecreted protein that has been reported to increase fat oxidation and improve insulin sensitivity. Our aim was to study the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

42
430
9
22

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 672 publications
(503 citation statements)
references
References 49 publications
42
430
9
22
Order By: Relevance
“…[23][24][25] It is therefore conceivable that the higher levels of insulin in insulin-resistant subjects may downregulate levels of adiponectin as suggested previously. 26,27 Although we have shown an inverse association between adiponectin and insulin resistance, it is obvious from Figure 2a that there was overlap of adiponectin levels between insulin-sensitive and insulinresistant patients and some of the insulin-sensitive individuals had low adiponectin. Some other studies have reported similar disassociation between adiponectin levels and insulin resistance 28,29 and the relationship between adiponectin and IR is probably not one of the direct cause and effect in all patients.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…[23][24][25] It is therefore conceivable that the higher levels of insulin in insulin-resistant subjects may downregulate levels of adiponectin as suggested previously. 26,27 Although we have shown an inverse association between adiponectin and insulin resistance, it is obvious from Figure 2a that there was overlap of adiponectin levels between insulin-sensitive and insulinresistant patients and some of the insulin-sensitive individuals had low adiponectin. Some other studies have reported similar disassociation between adiponectin levels and insulin resistance 28,29 and the relationship between adiponectin and IR is probably not one of the direct cause and effect in all patients.…”
Section: Discussionmentioning
confidence: 68%
“…Some other studies have reported similar disassociation between adiponectin levels and insulin resistance 28,29 and the relationship between adiponectin and IR is probably not one of the direct cause and effect in all patients. It is possible that their inverse relationship may be mediated not only by insulin levels but also by other hormones such as catecholamines or androgens, [30][31][32] as well as by pro-inflammatory cytokines, 33,34 and some medications. 31,35 Our results also depict the prominent role that adipose tissue plays in both insulin resistance and the clinical expression of the metabolic syndrome (Figures 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the current data also suggest that chronic hypoadiponectinaemia could provide a therapeutic target for risk modification in this patient population. In this respect, it is of interest to note that thiazolidinedione therapy, which has been shown to preserve beta cell function and significantly reduce the risk of developing type 2 diabetes in women with a history of GDM [37], is also known to increase adiponectin levels [38]. It thus emerges that a pathophysiological relationship between hypoadiponectinaemia and diabetic risk following GDM could hold important clinical implications.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with previous publications that thiazolidinedione increases plasma adiponectin levels in obese and in type 2 diabetic patients, as well as in normal subjects to a similar extent. This is accompanied by improvements in different metabolic variables in obese and diabetic, but not in lean insulin-sensitive subjects [40]. This discrepancy has been recently elucidated by the finding that it is not the absolute amount, but rather the distribution of low-and highmolecular weight adiponectin that is important for improved insulin sensitivity in the liver [11].…”
Section: Discussionmentioning
confidence: 99%